Projeto gráfico para um livro de receitas - Novinski, Luciane Chioccarello (2019)
This work was made as the final paper of Graphic Design Technology’s course at the Federal Tecnological University of Paraná, developed by the student Luciane Chioccarello Novinski, supervision by the teacher Alan Ricardo Witikoski. The main objective of this work was develop a graphic project for a family cookbook. Analasing old notebooks, cookbooks, other notes and objects that are part of this family collection and their memories related to cooking, as well. This paper registers the process of production and challenges of representing graphically these memories.